1988
DOI: 10.1111/j.1747-5457.1988.tb00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Regional Hydrogeology and Hydrocarbon Occurrences in Michigan, Usa

Abstract: Compilation of hydrologic data for deep aquifers in the Michigan Basin makes it feasible to test the hydraulic theory of hydrocarbon migration in Michigan. Comparison of equipotential sufaces and patterns of hydrocarbon deposits shows that commercial oil deposits in most aquifers and the more prollJic gas deposits in the St. Peter Sandstone are preferentially associated with regional groundwater discharge areas, as predicted by the hydraulic theoyy. Shallow natural gas deposits occur in regional groundwater re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The basal Cambrian-Ordovician aquifers in all three basins are principally comprised of sandstones and carbonates (dolomite and limestone), confined by the overlying Maquoketa grey shale (also referred to as the Utica Shale). The Silurian carbonates in the Michigan and Appalachian basins contain thick sequences ($1 km) of bedded halite and anhydrite, predominately in the Salina Group, which are relatively impermeable (Vugrinovich, 1988). Overlying Devonian carbonates also contain localized halite and anhydrite.…”
Section: Hydrogeologymentioning
confidence: 98%
“…The basal Cambrian-Ordovician aquifers in all three basins are principally comprised of sandstones and carbonates (dolomite and limestone), confined by the overlying Maquoketa grey shale (also referred to as the Utica Shale). The Silurian carbonates in the Michigan and Appalachian basins contain thick sequences ($1 km) of bedded halite and anhydrite, predominately in the Salina Group, which are relatively impermeable (Vugrinovich, 1988). Overlying Devonian carbonates also contain localized halite and anhydrite.…”
Section: Hydrogeologymentioning
confidence: 98%
“…The geochemical signatures reported here were observed in settings adjacent to regional lowland areas (Michigan Lowland area and Saginaw Lowland area; Figs. 6 and 7), supporting the conceptual model of a topographically driven, regionally focused groundwater flow system with the hydraulic potential for upward flow from deeper units within the Michigan Basin (Cartwright et al, 1979;Vugrinovich, 1986Vugrinovich, , 1988. Vugrinovich (1986, p. 8) reported that within the Devonian D3 aquifer unit, "[f]low is directed to topographic lows and outcrops beneath Lakes Huron, Michigan, and Erie."…”
Section: Michigan Basin Solute Fluxes To Great Lakes Sediments-other ...mentioning
confidence: 63%
“…Several Michigan Basin geological formations are known to contain Ca-rich brines (Frape et al, 1989;Wilson and Long, 1993b;Ma et al, 2005) and/or evaporite minerals, i.e., gypsum and anhydrite (Cvancara and Melik, 1961), but the extent to which these formations underlie southern Lake Huron (Fig. 1; Cvancara and Melik, 1961;Vugrinovich, 1986) or whether there exists sufficient hydraulic drive for cross-formational flow in this setting (Vugrinovich, 1988;Bahr et al, 1994) are not well known.…”
Section: Michigan Basin Solute Fluxes To Great Lakes Sediments-other ...mentioning
confidence: 99%
See 1 more Smart Citation